Analysis of EFL Learners' Writing Challenges in the Digital Era - Manggolo, Noor Sahid Kusuma Hadi; Arifin, M. Fatkhu; Indriani, Lilia; Khusniyati, Nurul Ngaini (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
The Writing Intensive Course emphasizes fundamental English writing elements, providing a prime chance for students to improve written communication. Educators face challenges in enhancing expressiveness, but the large millennial class size, familiar with digital technology, presents a potential advantage. Millennials, as digital natives, show enthusiasm for digital-context learning, offering an opportunity for effective instruction in writing. The primary objective of this research is to find out the problems or challenges students undergo while learning to write English in the digital era. This quantitative research examined 174 EFL students to give particular responses that work with brief reviews of their challenges in English writing. Unable to express (10.9%), improve skills (9.8%), and develop ideas (5.2%) in writing stand strong as the biggest three difficulties in English writing. The diverse challenges, collected from participant samples, reveal consistent issues for both active and nonactive students. The study emphasizes the value of digital-assisted courses, offering hope for enhanced English writing and communication skills among SL/FL learners in a more accessible and effective manner. In brief, this study highlights internal factors as the primary challenges in writing class, with students struggling with self-expression, doubts about improvement, and generating ideas. Various challenges, including optimizing roles and feedback, underscore the importance of addressing obstacles for enhanced writing proficiency in digital-assisted courses